IMPLEMENTING INQUIRY-BASED LEARNING AND EXAMINING THE EFFECTS IN JUNIOR COLLEGE PROBABILITY LESSONS - Jessie Siew Yin Chong; Maureen Siew Fang Chong; Masitah Shahrill; Nor Azura Abdullah (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2017)
This study examined how Year 12 students use their inquiry skills in solving conditional probability questions by means of Inquiry-Based Learning application. The participants consisted of 66 students of similar academic abilities in Mathematics, selected from three classes, along with their respective teachers. Observational rubric and lesson observation checklist were used as the data collection instruments. The results obtained were analyzed and then quantitatively reported. Findings from the observational rubric revealed that Year 12 students were able to understand most of the questions during the activity, but they only select and use one previously learned method to solve the questions during the activity. In addition, these students rarely seek and asked probing questions during the activity. They only used words, diagrams and numbers to interpret the solutions to the questions and make connections between them but with few mistakes detected.DOI:Â http://dx.doi.org/10.22342/jme.8.2.3964.157-164